TRANSFORMATION OF LIBERAL IDEOLOGY MIRRORED BY MODERN OLYMPICS: SCIENTIFIC ANALYSIS - Leskova, I.V.; Maksimova, E.V.; Peredelsky, A.A.; Chirtoaca, A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to provide scientific evidence for and forecast further progress of the Olympics in the context of modern Western economic, political and sociological research conventions, particularly fixed in the UNESCO materials and encyclopedic documents. Results and conclusion. We found the transformations of the Olympic movement and International Olympic Committee service in the late XIX to XX century replicating in every minor detail regresses of the liberal governance and its social scientific support service in Western countries as verified by the following: - It should be emphasized that in practical reality the Olympics has regressed into one of the key social institutions and pillars of the Western world and, hence, need to be theoretically analyzed within this frame clean of mythology, idealistic philosophy and other ideological manipulations with common public opinions.